ANALISIS PENGENDALIAN KUALITAS PROSES PENGANTONGAN SEMEN MENGGUNAKAN SIX SIGMA (STUDI KASUS PT. SEMEN BOSOWA BANYUWANGI) - Trio Yonathan Teja Kusuma; Dosep Guritno (Lembaga Penelitian dan Pengabdian pada Masyarakat, Universitas Buana Perjuangan Karawang, 2020)
The cement bagging process at PT Semen Bosowa Banyuwangi is still done simply using a check sheet. The percentage of defective products based on observational data on January 10-February 5 2020 is 0.39% which is at the four sigma level (4σ). This study focused on controlling the quality of the Bosowa Cement bagging process using the Six Sigma method with the DMAIC approach (Define, Measure, Analyze, Improve, Control) which aims to help control the quality of cement bags by reducing the number of defective products to reach the six sigma level (6σ). By using the tools CTQ, P-Chart, Sigma Level, Pareto Diagram, Fishbone Diagram and FMEA, the potential causes of damage that often occur diverter valve is problematic, and the position of the bag is stuck. saddle bag is not precise. Based on the cause of the damage, a solution was found in the form of routine preventive maintenance on each equipment in the packer area and inspections and sampling tests for the quality of the cement bags to be used.